2005
DOI: 10.1097/01.qai.0000141481.48348.7e
|View full text |Cite
|
Sign up to set email alerts
|

Unrecognized HIV Infection, Risk Behaviors, and Perceptions of Risk Among Young Men Who Have Sex With Men

Abstract: This study evaluated the magnitude and distribution of unrecognized HIV infection among young men who have sex with men (MSM) and of those with unrecognized infection, the prevalence and correlates of unprotected anal intercourse (UAI), perceived low risk for infection, and delayed HIV testing. MSM aged 15-29 years were approached, interviewed, counseled, and tested for HIV at 263 randomly sampled venues in 6 US cities from 1994-2000. Of 5649 MSM participants, 573 (10%) tested positive for HIV. Of these, 91% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
184
6
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(204 citation statements)
references
References 47 publications
12
184
6
2
Order By: Relevance
“…19 Furthermore, black men are estimated to have the highest number of unidentified HIV infections, 20 and studies have found that minority MSM (black, Hispanic, mixed race) were more likely to be unaware of their HIV infection. [21][22][23] Additionally, access to antiretroviral therapy which has been associated with reduced HIV transmission 24 is lower among black MSM. 25 Finally, it is possible that STD/HIV prevalence within the partner pool are related to the increases in P&S syphilis and HIV as young and minority MSM have higher rates of HIV and STD.…”
Section: Resultsmentioning
confidence: 99%
“…19 Furthermore, black men are estimated to have the highest number of unidentified HIV infections, 20 and studies have found that minority MSM (black, Hispanic, mixed race) were more likely to be unaware of their HIV infection. [21][22][23] Additionally, access to antiretroviral therapy which has been associated with reduced HIV transmission 24 is lower among black MSM. 25 Finally, it is possible that STD/HIV prevalence within the partner pool are related to the increases in P&S syphilis and HIV as young and minority MSM have higher rates of HIV and STD.…”
Section: Resultsmentioning
confidence: 99%
“…3 Among young men who have sex with men (YMSM), the racial/ethnic disparities in HIV are particularly pronounced. 4,5 Limited research has examined factors underlying racial/ethnic differences in HIV risk among YMSM. Harawa and colleagues found risky sex and drug use reported more frequently by Caucasian rather than Black YMSM, whereas Sifakis et al found race to be unassociated with risk behavior.…”
Section: Introductionmentioning
confidence: 99%
“…In the 35 states with long-term confidential name-based reporting through 2004, 62% of the 17,824 adolescents between the ages of 13-24 who were given either an HIV or AIDS diagnosis were males and 38% were females (CDC, 2005). Young men who have sex with men (YMSM) represent the largest group of males between the ages of 13-24 living with HIV and AIDS, and their rates of infection are increasing at alarming rates; especially among African American and Latino youth (CDC, 2001;CDC, 2005;Garofalo & Harper, 2003;MacKellar et al, 2005;Valleroy, MacKellar, Karon, & Rosen, 2000;Wolitski, Valdiserri, Denning, & Levine, 2001). Female adolescents of color also have disproportionately higher rates of infection with HIV than White females, especially those living in low-income urban environments (Aral, 2001;CDC, 2005;Krieger, Waterman, Chen, Soobader, & Subramanian, 2003).…”
Section: Introductionmentioning
confidence: 99%